U.S. Army weapons systems 2014-2015 (Skyhorse Publishing, 2014)
From the Advanced Threat Infrared Countermeasures to the XM320 grenade launcher, this comprehensive guide profiles nearly every weapon currently in use by the U.S. Army. In addition, it covers cutting-edge technology that will soon be employed by soldiers around the world. This book features:• missiles• biological detection systems• rockets• reconnaissance systems• bows and arrows (believe it or not) You name it, this book has it. Also included is a thorough discussion of Future Combat Systems (FCS), the system of systems that, when fully operational, will provide the army and the joint